Pro itu et pro reditu: the pottery offered in the sanctuaries along the mountain passes - Puppo, Paola (Rei Cretariae Romanae Fautorum Acta, 2022)
The Roman pottery of imperial date found in the sanctuary active from the 5th century BC to the 4th century AD at Great Saint Bernard (2473 a.s.l) is compared to the pottery found in the sanctuary above Col de Tende and to that of Roman Imperial period found in the sanctuary on the Sella of Valoria above Cisa Valico. Most of the pottery, dated to the 1st and the 2nd centuries AD, concerns common ware ('olle ovoidi', with evident cultual function), while only 37% is fine ware, particularly South Gaulish terra sigillata and thin-walled ware (above all gobelets with water leaves à la barbotine). Of the common ware - a dataset that can also be compared with that of the sanctuary at the Sella of Valoria- 'ovoids ollae' predominate, which were used as containers for offerings, and are often found in votive pits. In the sanctuary at Sella of Valoria the terra sigillata is absent, while the black gloss ware is represented by rare and minute fragments, dated to the 4th-3rd century BC. The element that alloys the sanctuaries is the fact that there are few amphorae (Lamboglia 2), so these were not an object of devotion but are indicators of the passage of commercial loads.